Health seeking behavior of the Bangladeshi migrant workers in Malaysia: some suggestive recommendations in adjustive context - Karim, A.H.M Zehadul; Mohamad Diah, Nurazzura (Canadian Center of Science and Education, 2015)
Background: Recently, there have been an increasing number of literatures on health seeking behavior of different segments of society in the urban and non-urban regions but rarely have these studies emphasized the health care issues related to migrant workers. With this paucity of investigation, this research focuses on the needs and assessment of Bangladeshi workers working in Malaysia and thus contextualizes it to their health care situation. Methodology and Data Sources: This study is an outcome of a baseline survey conducted in and around Kuala Lumpur city in Malaysia. Based on the snowball technique, the research identified a total of 200 workers through convenience random sampling and interviewed them face-to-face, most extensively with a set of structured questionnaire. The research was further supplemented by a few FGDs. Findings: Until recently, the bulk of migrant workers from Bangladesh come to Malaysia because of bilateral agreements signed by both governments from time to time since 1992. Among these Bangladeshi migrant workers, there is a lack of health facilities in part because of the absence of any precise specification in the agreements. Most of the Bangladeshi migrant workers in Malaysia therefore, are fully devoid of having any Medicare facilities from their respective place of employment and working farms. This is evident when it was pronounced by 87% of Bangladeshi workers who said clearly that they do not receive any medical support or health protection and privileges in times of necessity and crisis. Since they are not protected by any medical insurance whatsoever, they are always afraid of seeing a medical doctor or to visit any health clinics or hospitals. Moreover, due to not having proper documents and also because of other problems and complications, many illegal workers are often denied access to this medical assistance. Most of the workers for that reason either bring some medicine from their back homes or remain sick without getting any proper medical treatment. Conclusions and Recommendations: Because there are no specific agreements on health care issues between Bangladesh and Malaysia, it directs us to conclude that the health care aspects of the foreign workers which are their rights are being ignored. Although foreign workers in Malaysia are accorded equal rights with that of the locals, due to absence of any precise specification on health aspects, these workers are unable to get benefits from the system. For that reason, in the later part of the research, we have concluded with a recommendation saying that since Malaysia is providing placement for a huge number of Bangladeshi workers, it is therefore the government of Bangladesh who should provide initial health support to these workers through a team of medical professionals employed at their foreign mission located in this country.